Environmental T4-Family Bacteriophages Evolve to Escape Abortive Infection via Multiple Routes in a Bacterial Host Employing “Altruistic Suicide” through Type III Toxin-Antitoxin Systems - Chen, Bihe; Akusobi, Chidiebere; Fang, Xinzhe; Salmond, George P. C. (Frontiers in Microbiology, 2017)
Abortive infection is an anti-phage mechanism employed by a bacterium to initiate its own death upon phage infection. This reduces, or eliminates, production of viral progeny and protects clonal siblings in the bacterial population by an act akin to an “altruistic suicide”. Abortive infection can be mediated by a Type III toxin-antitoxin system called ToxINPa consisting of an endoribonuclease toxin and RNA antitoxin. ToxINPa is a heterohexameric quaternary complex in which pseudoknotted RNA inhibits the toxicity of the toxin until infection by certain phages causes destabilization of ToxINPa, leading to bacteriostasis and, eventually, lethality. However, it is still unknown why only certain phages are able to activate ToxINPa. To try to address this issue we first introduced ToxINPa into the Gram-negative enterobacterium, Serratia sp. ATCC 39006 (S 39006) and then isolated new environmental S 39006 phages that were scored for activation of ToxINPa and abortive infection capacity. We isolated three T4-like phages from a sewage treatment outflow point into the River Cam, each phage being isolated at least a year apart. These phages were susceptible to ToxINPa-mediated abortive infection but produced spontaneous “escape” mutants that were insensitive to ToxINPa. Analysis of these resistant mutants revealed three different routes of escaping ToxINPa, namely by mutating asiA (the product of which is a phage transcriptional co-activator); by mutating a conserved, yet functionally unknown, orf84; or by deleting a 6.5 kb-10 kb region of the phage genome. Analysis of these evolved escape mutants may help uncover the nature of the corresponding phage product(s) involved in activation of ToxINPa.